Stability Analysis of a Microgrid System With a Hybrid Offshore Wind and Ocean Energy Farm Fed to a Power Grid Through an HVDC Link; IEEE Transactions on Industry Applications; Vol. 54, iss. 3 - Li Wang; Lin Chun-Yu; Wu Hong-Yi; Prokhorov A. V. Anton Viktorovich (2018, 2018)
Title screen